The association between psychological distress, abusive experiences, and help-seeking among people with intimate partner violence - Bohan Zhang; Arkers Wong; Rose E. Constantino; Vivian Hui (BMC, 2024)
Abstract Background Intimate partner violence (IPV) is a serious public health problem associated with countless adverse physical and mental health outcomes. It places an enormous economic and public health burden on communities. The aim of this study was to examine the associations between psychological states (such as depression or hopeless) and help-seeking experiences of IPV survivors after experiencing IPV, based on the Allegheny County Health Survey (ACHS). Methods Data from 2015 to 2016 Allegheny County Health Survey with N = 8,012 adults were analyzed. The 6-item version of the Kessler Psychological Stress Scale, located in Module 11 of the ACHS questionnaire, was used to measure psychological stress in participants. Module 12 of the ACHS questionnaire collected information on participants' experiences of intimate partner violence and help-seeking in the past 12 months. Descriptive statistical analysis, Pearson's chi-square or two sample independent t-tests statistical analysis, and multivariate binary logistic regression models were used to analyze the relationship between IPV experience and psychological distress. Results A total of 212 of the 8,012 participants had IPV experience, with age, marital status, education, income, and race significantly different from those without IPV experience. The psychological stress of participants feeling hopeless (OR = 2.02, 95% CI = 1.37-2.99), restless or fidgety (OR = 1.83, 95% CI = 1.27-2.65), perceiving everything was an effort (OR = 1.55, 95% CI = 1.08-2.22) and worthless (OR = 1.49, 95% CI = 1.01-2.20) was associated with the IPV experience. Help-seeking behaviors of IPV survivors were associated with psychological distress, such as hopelessness (OR = 6.71, 95% CI = 1.38-32.60). Conclusions This study explored the association between IPV experience, help-seeking and psychological distress, and the need to expand community support. It is necessary to implement targeted interventions, enhance training of professionals, and promote the identification of early IPV cases as well as collaboration between healthcare and social support departments to reduce the occurrence of IPV or psychological distress following IPV.